IGF-Binding Proteins, Adiponectin, and Survival in Metastatic Colorectal Cancer: Results From CALGB (Alliance)/SWOG 80405. Issue 1 (27th August 2020) - Guercio, Brendan J; Zhang, Sui; Ou, Fang-Shu; Venook, Alan P; Niedzwiecki, Donna; Lenz, Heinz-Josef; Innocenti, Federico; Pollak, Michael N; Nixon, Andrew B; Mullen, Brian C; O'Neil, Bert H; Shaw, James E; et al.
Abstract: Background: Energy balance-related biomarkers are associated with risk and prognosis of various malignancies. Their relationship to survival in metastatic colorectal cancer (mCRC) requires further study. Methods: Baseline plasma insulin-like growth factor (IGF)-1, IGF-binding protein (IGFBP)-3, IGFBP-7, C-peptide, and adiponectin were measured at time of trial registration in a prospective cohort of patients with mCRC participating in a National Cancer Institute–sponsored trial of first-line systemic therapy. We used Cox proportional hazards regression to adjust for confounders and examine associations of each biomarker with overall survival (OS) and progression-free survival (PFS). P values are 2-sided. Results: Median follow-up for 1086 patients was 6.2 years. Compared with patients in the lowest IGFBP-3 quintile, patients in the highest IGFBP-3 quintile experienced an adjusted hazard ratio (HR) for OS of 0.57 (95% confidence interval [CI] = 0.42 to 0.78; P nonlinearity < .001) and for PFS of 0.61 (95% CI = 0.45 to 0.82; P trend = .003). Compared with patients in the lowest IGFBP-7 quintile, patients in the highest IGFBP-7 quintile experienced an adjusted hazard ratio for OS of 1.60 (95% CI = 1.30 to 1.97; P trend < .001) and for PFS of 1.38 (95% CI = 1.13 to 1.69; P trend < .001). Plasma C-peptide and IGF-1 were not associated with patient outcomes. Adiponectin was not associated with OS; there was a nonlinear U-shaped association between adiponectin and PFS ( P nonlinearity = .03). Conclusions: Among patients with mCRC, high plasma IGFBP-3 and low IGFBP-7 were associated with longer OS and PFS. Extreme levels of adiponectin were associated with shorter PFS. These findings suggest potential avenues for prognostic and therapeutic innovation.